Editorial. (28th March 2023) - Viennet, Carole; Ghezelbash, Daniel; Hinterberger, Kevin Fredy; Urscheler, Lukas Heckendorn
This special issue represents the first attempt to take stock of and define the emerging field of comparative migration law. It aims to reflect on the purpose and methods of comparative migration law, identify key contemporary debates and chart a program for future research. It does so by drawing on contributions from academics working across a number of inter-related fields, including migration law, refugee law, comparative law, comparative international law and social sciences. The starting point was a conference held in Lausanne at the Swiss Institute of Comparative Law on 4 December 2019 where we had the opportunity to begin developing the ideas and arguments explored in this special issue. The ideas presented in the contributions are not intended to define or limit the field of comparative migration law rather the intention is to spark a discussion about the future directions of research in this area.